New insights into the nature of the bandgap of CuGeO3 nanofibers: Synthesis, electronic structure, and optical and photocatalytic properties. (March 2021) - Suzuki, V.Y.; Amorin, L.H.C.; de Paula, N.H.; Albuquerque, A.R.; Li, M. Siu; Sambrano, J.R.; Longo, E.; La Porta, F.A.
Abstract: The influence of the surfactant on the physical properties of CuGeO3 (CGO) nanocrystals synthesized from a microwave-assisted hydrothermal method is discussed by a combination of experimental and theoretical approaches. Our results, however, revealed that the surfactant has a critical role in the stabilization of the desired orthorhombic CGO structure consist of many well-defined long nanofibers with a median diameter and the dispersion size of 9.1 nm and 3.7 nm, respectively. These findings confirm that these samples experimentally have a direct band gap (at about 2.74–2.93 eV) and also that the hybrid Heyd–Scuseria–Ernzerhof (HSE06) is the density functional most recommended for the computational simulations of these systems. All the synthesized materials presented a broad photoluminescence band centered at the blue region, with two characteristic emission peaks, at about 2.55 eV and 2.80 eV, respectively. Our champion catalyst (CGO (40 %)) degrades 50 % of the methylene blue solution for about 60 min.